Common chemical halts soil erosion - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
In the eastern part of the USA, in Magic Valley, farmers can be seen throwing handfuls of white crystals into their irrigation water. Almost immediately the water turns from murky brown to crystal clear. The crystals are the latest way to stop soil...